2006
DOI: 10.1097/01.aids.0000199829.57112.2f
|View full text |Cite
|
Sign up to set email alerts
|

CD4 cell recovery in treated HIV-2-infected adults is lower than expected: results from the French ANRS CO5 HIV-2 cohort

Abstract: In 61 antiretroviral-naive HIV-2-infected patients starting triple therapy at a median CD4 cell count of 136 cells/microl, the median increase was 41 cells/microl at month 12, which was no different among those on protease inhibitors or triple nucleoside analogues. Despite virological response, as the median plasma load was under the detectable threshold from month 3, CD4 cell recovery remained poor in treated HIV-2 infection. Our results raise the question of the optimal regimen to recommend in HIV-2-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
5
30
0
2
Order By: Relevance
“…Possible reasons may include the use of ineffective ART regimens for HIV-2, poorer ART adherence related to the greater complexity of a protease inhibitor-containing ART regimen, and/or possibly a biological phenomenon related to older age (HIV-2 patients generally being older than HIV-1 patients on ART). Furthermore, this immunological difference between HIV-1 and HIV-2 has been previously reported in France, 29,30 and it has been suggested that although disease progression with HIV-2 is slower, there may be a lower intrinsic immune recovery in HIV-2 patients with severe immune deficiency than in HIV-1 patients. 29 If the difference seen in our study is underpinned by permanent immune damage occurring in severely immune-deficient HIV-2 patients, it would justify the need for earlier ART initiation in these patients.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Possible reasons may include the use of ineffective ART regimens for HIV-2, poorer ART adherence related to the greater complexity of a protease inhibitor-containing ART regimen, and/or possibly a biological phenomenon related to older age (HIV-2 patients generally being older than HIV-1 patients on ART). Furthermore, this immunological difference between HIV-1 and HIV-2 has been previously reported in France, 29,30 and it has been suggested that although disease progression with HIV-2 is slower, there may be a lower intrinsic immune recovery in HIV-2 patients with severe immune deficiency than in HIV-1 patients. 29 If the difference seen in our study is underpinned by permanent immune damage occurring in severely immune-deficient HIV-2 patients, it would justify the need for earlier ART initiation in these patients.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, this immunological difference between HIV-1 and HIV-2 has been previously reported in France, 29,30 and it has been suggested that although disease progression with HIV-2 is slower, there may be a lower intrinsic immune recovery in HIV-2 patients with severe immune deficiency than in HIV-1 patients. 29 If the difference seen in our study is underpinned by permanent immune damage occurring in severely immune-deficient HIV-2 patients, it would justify the need for earlier ART initiation in these patients. It would also imply that many HIV-2 patients who do not achieve threshold-level increases in CD4 counts would need indefinitely to continue adjunctive trimethoprim-sulfamethoxazole and other prophylaxis against opportunistic infections.…”
Section: Discussionsupporting
confidence: 67%
“…13,14 In HIV-2 infections, better virological and immunological outcomes are seen with protease inhibitor (PI)-containing regimens compared to nucleosidic reverse transcriptase inhibitor (NRTI)-only regimens, 15,16 although some authors see no marked differences. 14,17 Sensitivity to ARV drugs differs between HIV-1 and HIV-2. HIV-2 is naturally resistant to nonnucleosidic reverse transcripase inhitors (NNRTI) and fusion inhibitors (FI).…”
Section: Introduction Hmentioning
confidence: 99%
“…In France, as recommended by the national expert group on the treatment of HIV infection, HIV-2-infected patients receive highly active antiretroviral therapy (HAART) regimens as HIV-1-infected individuals do, except without nonnucleoside reverse transcriptase inhibitors or fusion inhibitor classes (17,12). However, a recent study showed that CD4 cell recovery was poor in antiretroviral-naive HIV-2-infected patients starting treatment with HAART (8). Thus, it appears crucial to determine HIV-2 susceptibility to the current protease inhibitors (PIs) available in order to define the optimal regimen to be recommended.…”
mentioning
confidence: 99%